Geometric Design of Upper Cisokan Hydroelectric Power Plant Access Road with AutoCAD® Civil 3D (STA 3+000 - STA. 4+800) - Arifin, Adlin; Rifai, Andri Irfan; S, Muhammad Rizal (DAS Institute, 2022)
The project to upgrade the access road to the Cisokan hydroelectric power plant and handle landslides is known as the Upper Cisokan Hydroelectric Power Plant Access Road Project. This access road has been a plan and completed build by PT. Pembangunan Perumahan (Persero) Tbk in 2019. There are several geometric alignments of the road with sharp curves. In this paper, the author intends to make a geometric plan for a new road in an area of STA. 3+000 – STA. 4+800. Planning is carried out using the AutoCAD® Civil 3D application for more effective and efficient results. The research method used is the Qualitative Method. The data source is obtained from the project data of the contractor, an access road to the Upper Cisokan hydroelectric power plant, and a reference to the Road Geometric Design Guidelines in 2021. Contour data is obtained from Google Earth® and processed using the Global Mapper® application. Planning is carried out by determining the design criteria of the road under review. Then the design criteria are used as a reference in making horizontal alignments, vertical alignments, superelevation, road assemblies, and corridor planning. The results of the planning obtained seven curves of horizontal and five curves of vertical. Furthermore, the AutoCAD® Civil 3D application is more effective and efficient because the process is relatively fast and easy, and changes to an item can be directly connected to all items.